Identifikasi Jenis, Pemetaan, dan Penanganan Limbah Bahan Berbahaya dan Beracun Pada PT Kaltim Parna Industri - Novia Setyawati; Febrianti, Nia (LPPM ITK, 2024)
PT Kaltim Parna Industri is a business entity engaged in the petrochemical industry which has the potential to produce hazardous and toxic waste (B3). This study aims to determine the type, mapping, and handling of hazardous and toxic waste (B3). The research method is by conducting a literature study and collecting existing data in the form of documents from companies and documentation. Based on the results of identification of the types, mapping, and handling of hazardous and toxic waste at PT Kaltim Parna Industri, it can be concluded that there are types of B3 waste generated from specific sources, and non-specific sources belonging to category 1 and category 2. The waste generated comes from activities in the process and utility areas. The handling that has been carried out when there is a potential for liquid B3 waste spills is by providing spill kits in the form of universal spill kits and chemical spill kits. Meanwhile, solid B3 waste can be disposed of in a special B3 waste bin that has been provided in the factory field area or directly to the B3 waste TPS.